2018
DOI: 10.1590/0074-02760180200
|View full text |Cite
|
Sign up to set email alerts
|

Meglumine antimoniate intralesional infiltration for localised cutaneous leishmaniasis: a single arm, open label, phase II clinical trial

Abstract: BACKGROUND Cutaneous leishmaniasis (CL) is a world-wide health problem which currently lacks effective, affordable and easy to use therapy. Recently, the meglumine antimoniate (MA) intralesional infiltration was included among the acceptable therapies for New World leishmaniasis. While this approach is attractive, there is currently little evidence to support its use in Americas.OBJECTIVES The aim of this study was to provide information about effectiveness and safety of a standardised MA intralesional infiltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 14 publications
0
15
0
2
Order By: Relevance
“…The cure rate related to EV-MA treatment was obtained from a previously published systematic review [2], while the cure rate related to IL-MA was extracted from an open-label phase II clinical trial [4]. According to the systematic review performed by Tuon et al (2008), the cure rate for the 310 Brazilian CL patients treated with MA by the parenteral route was 71.3% [13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cure rate related to EV-MA treatment was obtained from a previously published systematic review [2], while the cure rate related to IL-MA was extracted from an open-label phase II clinical trial [4]. According to the systematic review performed by Tuon et al (2008), the cure rate for the 310 Brazilian CL patients treated with MA by the parenteral route was 71.3% [13].…”
Section: Methodsmentioning
confidence: 99%
“…The risk of developing ML, a complication caused by Leishmania braziliensis , is probably the main reason for the almost exclusively parenteral therapies used for CL in the Americas. This paradigm has been only recently overcome, which has allowed the accumulation of experience with topical and local treatments, including antimony intralesional infiltration [4], [5] [7]. Specifically, besides a systematic review gathering 5679 patients (global cure rate of 75%, IC 95% 68–81%), a single arm clinical study in Brazil has showed a cure rate of 87% (95% CI: 77–96%) and minimal systemic side effects with meglumine antimoniate intralesional infiltration approach [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En cambio este tipo de efectos adversos en la aplicación intralesional son considerados raros 25 . El dolor local se presentó en todos los casos independientemente de si el tratamiento fue por aplicación sistémica o intralesional debido a la hipersensibilidad local del tejido inflamado por la toxicidad del antimonio 26,27 y en caso de la aplicación intralesional además la inflamación responde a la actividad del parasito presente en el borde de las lesiones 28,29 .…”
Section: Discussionunclassified
“…However, there are a number of limitations with these drugs including cost, efficacy, adverse effects and duration of treatment. Considering the epidemiological impact of Leishmaniasis, development of safe, effective and affordable treatment option remains a concern 2,11…”
Section: Introductionmentioning
confidence: 99%